KAIDAH FIKIH DALAM REAKTUALISASI HUKUM ISLAM - Irwandi Irwandi (SYARIAH: Journal of Islamic Law, 2022)
Human life continues to develop in accordance with its human nature, making many new cases appear without any legal provisions in either the Al-Quran or Hadith. The dynamics of society that continues to develop are not in line with legal texts which are static in nature. Based on these conditions, it is necessary to actualize Islamic law. Another problem that arises is that in order to carry out reactualization, there must still be a mechanism or formula for discovering the new law. The fiqh rules actually provide a concrete solution to the need for a method or way of finding the law (istinbath al-ahkam). With the existence of fiqh principles, it is hoped that the answers to contemporary problems can be found as an application to the re-actualization of Islamic law.